PELATIHAN ENGLISH FOR JOB HUNTING DI MADRASAH DINIYAH BABA AL HIKMAH DI DESA JINGGLONG, SUTOJAYAN, BLITAR. - sholikhi, fu'ad (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2022)
Abstract Many firms today only search for the finest quality human resource. Those organizations ignore people with poor communication skills because they want employees who can successfully communicate in both English and the local language. During the interview, the job seeker must deal with the English language, and job interview skills are not generally taught in formal schools. The goal of this program is to use the team-teaching method to deliver English for Job Hunting Training to 16 students at Baba Al Hikmah. This method contains English Interview Tips and Tricks, as well as understanding Curriculum Vitae and Resume, are included in this strategy. To do so, the author utilizes 4 techniques (planning, implementation, observation, and evaluation) to solve the studentsâ€™ problem at Baba Al Hikmah. With the help of this training, the students have better knowledge in English for Job Hunting (Interview, Curriculum Vitae, Resume), have a stronger desire to learn English, and have new English Vocabularies. It is hoped that the training can be a stepping-stone to deal with Job Interviews at a foreign company. Keywords: job hunting; interview; English; curriculum vitae